Chest wall strapping in a porcine model: Dynamic dysanapsis dilates airways for optimized function of the “oversized” lung - Eric Abston; Michael Eberlein (JHLT Open)
Chest-Wall-Strapping (CWS), a technique forcing the lung to operate at low volumes, is a model for an oversized lung allograft. Dynamic-dysanapsis describes airway dilation mediated by increased elastic recoil from CWS. We hypothesized that Dynamic-dysanapsis can be quantified via the Dysanapsis-Ratio, defined as the airway-size to lung-volume ratio.Farm-raised pigs (n=3) were mechanically ventilated. Stepwise CT-images throughout the lung deflation limb in control and CWS conditions were analyzed quantifying airway dimensions and lung volume.CWS (30%-reduction in lung-volume) was associated with a significant increase in the Dysanapsis-Ratio (p<0.001). CWS increased airway distensibility at the 6th major branch of the right lower airway (27±7% vs. 39±5%, p=0.04).The dysanapsis-ratio allows quantification of dynamic-dysanapsis with CWS. Dynamic-dysanapsis appears to be a compensatory mechanism to preserve pulmonary gas exchange by airway dilation when the lung is forced to operate at lower lung volumes. Dynamic-dysanapsis furthers the understanding of oversized allografts in lung transplantation.